The health impact of climate change on the women in reproductive age: a study of coastal communities in Satkhira, Bangladesh - Amin, Md. Noman; Hossain, Md. Alamgir; Islam, Md. Rakibul; Mondal, Sabuj; Ali, Md. Hossain (Frontiers in Public Health, 2025)
BackgroundClimate change and health issues pose a global threat, particularly in developing countries like Bangladesh. Within the socio-economic structure in coastal regions, women played a crucial role in contributing livelihood and living resources, while new climatic ecology creates chaotic relationships between environment and human health. The emerging adverse climatic ecology is directly and indirectly affecting them in the sphere of their both outdoor and indoor activism. This study explores the health impacts of climate change on the women of reproductive age (ages between 14 and 49 from the Bangladeshi perspective) living in coastal communities, i.e., Satkhira, Bangladesh.MethodsTo choose study locations, this study conducted a literature survey to find out the most vulnerable coastal region of Bangladesh. The study has selected the five most vulnerable unions of Shyamnagar upazila in Satkhira district. This study adopted a multi-method approach combining in-depth interviews and KIIs. Based on this methodological guide, this study interviewed 25 women and 5 married men, while their responses have further been supplemented and validated by KIIs with health workers and medical officers.ResultsFindings show that climate change posture to new climatic ecology facilitating adverse situations that lead to the intrusion of saline water within communities, lack of fresh and drinkable water, women exposure to waterborne diseases resulting from both salinity and scarcity of fresh usable water, skin disorders, gynaecological and reproductive illnesses, and vector-borne diseases. Women also bear an encountered burden in their struggle to acquire water and good health, including limited hygiene facilities and maternal care. This dilemma is even worsened during the summer season, which exposes women to heat waves, resulting in physical complications such as anaemia, pregnancy risks, heat stroke, dehydration, hypertension and psychological complications like anxiety, stress and depression.ConclusionBreaches in awareness and prevention practices were outlined from the study, as there is a need to realize integrated solutions to address the environmental and health challenges of the populations. Further, there is an absolute need to continue improving access to safe water, healthcare services, and education as a way to build resilience in affected communities.